2011
DOI: 10.3390/pharmaceutics3040954
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and in Vitro, ex Vivo and in Vivo Evaluation of Elastic Liposomes for Transdermal Delivery of Ketorolac Tromethamine

Abstract: The objective of the current study was to formulate ketorolac tromethamine-loaded elastic liposomes and evaluate their in vitro drug release and their ex vivo and in vivo transdermal delivery. Ketorolac tromethamine (KT), which is a potent analgesic, was formulated in elastic liposomes using Tween 80 as an edge activator. The elastic vesicles were prepared by film hydration after optimizing the sonication time and number of extrusions. The vesicles exhibited an entrapment efficiency of 73 ± 11%, vesicle size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 30 publications
2
29
0
3
Order By: Relevance
“…The obtained results (Table 1) demonstrated that, by using PL90G, PL80H and PL90H the EE were found approximately 86.67, 74.58 and 80.62% at 1:1 ratio of CH: PL. The results were consistent with previous published reports 36 . Thus, it can be concluded that, stoichio-metric ratio between cholesterol and phospholipids, in addition to selection of proper phospholipids with highest phosphatidylcholine content might be responsible for obtaining highest EE.…”
Section: Results and Discussion: Entrapment Efficiencysupporting
confidence: 94%
“…The obtained results (Table 1) demonstrated that, by using PL90G, PL80H and PL90H the EE were found approximately 86.67, 74.58 and 80.62% at 1:1 ratio of CH: PL. The results were consistent with previous published reports 36 . Thus, it can be concluded that, stoichio-metric ratio between cholesterol and phospholipids, in addition to selection of proper phospholipids with highest phosphatidylcholine content might be responsible for obtaining highest EE.…”
Section: Results and Discussion: Entrapment Efficiencysupporting
confidence: 94%
“…highest incorporation of PT in liposomal vesicles was found to be enhanced by increasing the ratios between CH and phospholipids, but then declined suddenly as further increasing the ratio. The results were consistent with previously published reports [37]. Thus, it can be concluded that a stoichiometric ratio between CH and phospholipids, in addition to the selection of proper phospholipids with highest phosphatidylcholine content, might be responsible for obtaining highest EE.…”
Section: Entrapment Efficiencysupporting
confidence: 93%
“…82,83 A good correlation between the permeation flux (permeation flux of 0.278 µg/cm 2 /h) and TEWL was found. 83 Another report studied ketorolac interactions (chemical stability) with the lipid bilayer of ELs using double-chain (sucrose laurate ester) and single-chain surfactants (octaoxyethylenelaurate ester). 84 Hydrophilic diclofenac sodium has been delivered in ELs and conventional liposomes to observe the effect of vehicles on in vitro drug-release patterns.…”
mentioning
confidence: 77%
“…22,82,83 These drugs are used in the treatment of moderate to severe pain, severe fever, postoperative pain, visceral pain of cancer, edema of traumatic condition, inflammation, and related consequences. However, many side effects have been associated with their use in conventional oral dosage, which limits their clinical efficacy.…”
Section: Steroidal and Nonsteroidal Analgesic Drugsmentioning
confidence: 99%
See 1 more Smart Citation